Implementasi Hak Pendidikan Anak Pada Lembaga Pembinaan Khusus Anak Kantor Wilayah II Jakarta - Anwar Sadat, Tyastiti Chandrawati; Permatasari, Pita (Jurnal Suara Hukum, 2023)
The importance of protecting children’s right is a legal obligation for Indonesia. One of The national goal of Indonesia that contained in prambule of constitution is to educate the life of the nation, either way through protecting the right to education for fostered children. The urgency of this research is to see the implementation of the children who must be protected in Indonesia. The formulation of the problems in this research are : 1) How is the implementation of the right to education of children at LPKA Regional Office II Jakarta? 2) what are the obstacles to the implementation of the right to education of children at LPKA Regional Office II Jakarta?. This research is empirical legal research using primary and secondary data. The approach in this research are statutory research and conseptual approach. The results of the research showed that the implementation has been done even thougt it was not fully in accordance with the regulation (The decision of Minister of Law and Human Rights about Guidelines for the treatment of children in Bapas, LPAS, dan LPKA 2014). The obstancles to the implementation of the right to education of children at LPKA Regional Office II Jakarta are infrastructures consisting of inadequate classrooms, sufficient stationery, and teachers who not apply pedagogical competencies.